Creativity based on new technologies in design of age-friendly cities: Polish seniors about their needs – research reflection - Dutka, Grzegorz; Gawron, Grzegorz; Rojek-Adamek, Paulina (Creativity Studies, 2021)
The identified changes in age structure on a global and local scale pose a major challenge for modern societies. And so, the issue of adapting urban spaces to the needs of older people has become of particular interest. But the intensity of changes requires a creative approach to this matter. One of the responses to this phenomenon has been the World Health Organization proposal to build age-friendly cities and communities. It details how to effectively reduce social and spatial exclusion experienced by older people. Importantly, the needs of the elderly are increasingly being taken into consideration during the design process. This article provides the theoretical explanation of the issues related to the creative solutions based on new technologies in the perspective of building an age-friendly city. The empirical section presents selected survey results conducted among Polish seniors which focus on three main aspects of new technologies: the current importance for seniors; the current state of solutions in the city; the predicted importance in the future.